Pelvic Vascular Malformations - Christenson, Brian M.; Gipson, Matthew G.; Smith, Mitchell T. (Seminars in Interventional Radiology, 2013)
Vascular malformations (VMs) comprise a wide spectrum of lesions that are classified by content and flow characteristics. These lesions, occurring in both focal and diffuse forms, can involve any organ and tissue plane and can cause significant morbidity in both children and adults. Since treatment strategy depends on the type of malformation, correct diagnosis and classification of a vascular lesion are crucial. Slow-flow VMs (venous and lymphatic malformations) are often treated by sclerotherapy, whereas fast-flow lesions (arteriovenous malformations) are generally managed with embolization. In addition, some cases of VMs are best treated surgically. This review will present an overview of VMs in the female pelvis as well as a discussion of endovascular therapeutic techniques.
Keywords: interventional radiology; vascular malformations; endovascular treatment; arteriovenous malformations; lymphatic malformations; venous malformations